SCHOOL SETTING AND VOIDING HABITS: A CROSS-SECTIONAL STUDY AMONG SCHOOL-AGED CHILDREN FROM THE FEDERAL DISTRICT. - Feitosa Salviano, Cristiane; Martins, Gisele (Ciencia, Cuidado e Saude)
This was a cross-sectional study conducted in 8 public and private schools of Riacho Fundo (Federal District), with children between 6 and 12 years old, that aimed to evaluate their frequency of going to the school restroom and permission to use it from the children's perspective, as well as to measure the rate of occurrence and impact of the experience of having had some once in a lifetime urinary leakage in the school setting. Data collection included interviews with key questions developed by the researchers. Data analysis included basic techniques of exploratory data analysis such as absolute and relative frequencies calculated using the Statistical Package for Social Sciences program. Out of 86 participating children, 73% (n = 63) reported going every day to the school restroom while those reporting not going pointed out reasons as they did not need to, lack of toilet paper, and lack of privacy or problems with the stalls' doors. Regarding permission to use the restroom, 66% (n = 57) stated being allowed to go whenever they needed. The experience of urinary incontinence at school was reported by 17 (20%) children and presented as a highly negative impact from their perspective.